Osobennosti pravovogo regulirovanija truda professional'nych sportsmenov - Sevcenko, O. A. (Teorija i Praktika fiziceskoj Kul'tury, 2005)
The article is devoted to the research of labor-legal relations of professional sportsmen. Blanks in the existing legislation regulating their professional work are revealed. The opportunity of the appendant applications of norms of civil law to the labor relations of sportsmen and the necessity of development of the special law is shown.